Group Coloring Therapy As Trauma Healing For Child Community Affected By Mount Semeru Eruption: A Case Study - Rahmawati, Ira; Sulistyorini, Lantin; Septiyono, Eka Afdi; Juliningrum, Peni Perdani; Merina, Nuning Dwi; Rizanti, Ayunda Puteri (Journal of Rural Community Nursing Practice, 2023)
Children are one of the populations most affected by the eruption of Mount Semeru. Post-disaster trauma can have a higher risk of producing post-traumatic stress disorder compared to other traumatic events. Group coloring play therapy can be an intervention that can reduce traumatic feelings by helping children express traumatic feelings, feel relaxed, and restore children's ability to interact with children around them. This research uses a case study method with the target of children who experience anxiety due to traumatic experiences of the eruption of Mount Semeru, The ages of the children in this study were categorized into two groups, namely children aged 1-5 years (45.9%) and children aged 6-11 years (54.1%), Evaluation in the intervention program is divided into 3 parts (the structure, process evaluation, and results during activities where children affected by the eruption of Mount Semeru are happy with the activities carried out and are able to interact with group mates. Group play therapy is able to have a positive impact on children affected by the Semeru eruption. after the intervention. children are able to express their traumatic feelings, are able to interact between team members, and show a happy and enthusiastic attitude during therapy.